Evaluation of spinal deformity and its progression in pyogenic spondylodiscitis: A retrospective MRI study of 59 cases - Andreas Kramer; Jonathan Neuhoff; Santhosh G. Thavarajasingam; Rebecca Sutherland; Hugh McCaughan; Benjamin Davies; Ehab Shiban; Florian Ringel; Andreas K. Demetriades (Brain and Spine)
Introduction: Pyogenic spondylodiscitis management often remains conservative without surgical intervention, yet the risk of spinal deformity under such therapy is unclear. Research question: This study explores spinal deformity progression in conservatively treated patients and identifies predictive factors for deformity advancement. Material and methods: Retrospective cohort design with radiological data analysis from 59 patients with conservatively treated pyogenic spondylodiscitis. Deformities were categorized into four progression types reflecting severity: Type 1 (progressive vertebral body edema/endplate erosion), Type 2 (Type 1 plus disc space collapse), Type 3 (vertebral body destruction/mild translation), and Type 4 (significant segmental kyphosis >20°/severe translation). Results: Among 59 patients, 66% exhibited progressive deformity over a mean follow-up of 10.75 months. The distribution of deformity progression was: Type 1 in two cases (3%), Type 2 in seven cases (12%), Type 3 in 13 cases (22%), and Type 4 in 17 cases (29%). Progression of deformity included a 92% increase in cases with segmental kyphosis >20°; and a 167% increase in cases with segmental translation. Risk factors for significant kyphosis included >50% vertebral body erosive destruction (p < 0.01) and the presence of an epidural abscess (p < 0.05). Lumbar region involvement significantly reduced the likelihood of spinal fusion at follow-up (p < 0.05). A paravertebral abscess was significantly associated with the presence of a fractured vertebrae at follow-up (p < 0.05). Discussion and conclusion: This study underscores the importance of closely monitoring patients with conservatively managed pyogenic spondylodiscitis for progressive spinal deformity, and suggests considering early surgical intervention in cases with a high risk of progression.